Analysis of species attributes to determine dominant environmental drivers, illustrated by species decline in the Netherlands since the 1950s. (March 2018) - Musters, C.J.M.; van Bodegom, Peter M.
Abstract: The relative impact of climate change and land use change on biodiversity loss is still under discussion. To alleviate drawbacks related to the use of observed species distributions, we introduce a novel approach to separate the effects of climate change and land use change, the latter split into fragmentation, agricultural intensification and reforestation. This approach, coined the Attribute Importance Analysis (AIA), uses the ability of species attributes to explain population declines. Through the a priori association between attributes and individual drivers, the relative importance of the drivers in causing the species decline can be assessed. We tested this approach on the population decline of vertebrate, insect, vascular plant, and fungi species in the Netherlands since the 1950s. Fragmentation was clearly the strongest driver of species decline for vertebrates and plants, and this may also be true for insects. For fungi, climate change seems the only driver. We found a weak signal of the importance of agricultural intensification for the decline of vertebrates only. We ascribe this unexpected low importance of agricultural intensification to our partitioning of agricultural effects into fragmentation and intensification. Our generic approach can offer valuable quantitative information on the relative importance of drivers that change local community composition without the need for spatial explicit information. Without data on temporal trends in drivers, including local climate and land use change, accurate information on species decline, species attribute values and association of attributes with drivers can give insights into the causes of species decline, which, in turn, can be used to adapt nature management accordingly.